2016
DOI: 10.1097/hjh.0000000000000985
|View full text |Cite
|
Sign up to set email alerts
|

Head orientation should be considered in ultrasound studies on carotid artery distensibility

Abstract: We conclude that consistent head rotation during a CCA ultrasound assessment causes a significant and clinically relevant bias in carotid artery distension measurements. The impact of unstandardized use of head rotation in studies with carotid distensibility as an outcome measure can therefore not be neglected; thus, standardization is highly recommendable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
(10 reference statements)
1
17
0
Order By: Relevance
“…The measurement protocol and data used in the present study are elaborated by Holtackers et al. ( 2016 ). Briefly, twelve apparently healthy volunteers ( , 6 males, 6 females) were recruited.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement protocol and data used in the present study are elaborated by Holtackers et al. ( 2016 ). Briefly, twelve apparently healthy volunteers ( , 6 males, 6 females) were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…For these purposes, a large set of virtual pressure ( P ), diameter ( D ), and intima–media thickness (IMT) measurements will be generated by sampling the measurement distributions of previously published P , D , and IMT measurements in healthy volunteers (Holtackers et al. 2016 ). For each D - P sample, we will obtain continuous D - P curves over the diastolic–systolic pressure range, using the single-exponential function introduced by Hayashi et al.…”
Section: Introductionmentioning
confidence: 99%
“…There is a direct coupling between axial and circumferential behavior, implying that nonphysiological axial behavior will also affect circumferential behavior and thus the overall modeling outcome (59). This coupling was illustrated by Holtackers et al (52), who showed that in vivo in volunteers, a change in carotid axial stretch induced by rotation of the head is detectible in the circumferential pressure-diameter relationship. From ex vivo biomechanical experiments, we know that axial force remains approximately constant over a wide range of transmural pressures (17,146,152).…”
Section: H702mentioning
confidence: 99%
“…We recently set out to quantitatively assess the physiological confounders of PWV [1], investigating the magnitude of their effect and ways to correct for them. These confounders included blood pressure [6,7,8], heart rate [9,10], and axial stretch [11]. This mini-review will concentrate on blood pressure as a confounder of PWV, and will discuss several options to deal with the confounding effect.…”
Section: Arterial Stiffnessmentioning
confidence: 99%